Touching and being touched: where knowing and feeling meet - Fischman, Lawrence (Frontiers in Psychology, 2023)
Philosophers maintain that touch confers a sense of reality or grounding to perceptual experience. In touching oneself, one is simultaneously both subject and object of touch, a template for experiencing oneself as subject and object of intentions, feelings, and motivations, or intersubjectivity. Here, I explore a form of self-touch carefully documented by Winnicott in observing how the infant engages the transitional object. I compare the processes of self-loss in transitional states, including absorption in art, empathic immersion, drug-induced ego dissolution, and depersonalization. I use examples drawn from Rodin, Dante, and the Beatles; research correlating neurophysiological findings with aspects of self-representation; predictive processing-based models; Howhy’s concepts of minimal and narrative self; Clark’s notion of the extended mind; and phenomenological perspectives on touch, to postulate a role for self-touch in the pre-reflective sense of mine-ness, or grounding, in transitional states.